PENGARUH UKURAN PERUSAHAAN, VARIABILITAS PERSEDIAAN, KEPEMILIKAN MANAJERIAL, FINANCIAL LEVERAGE DAN LABA SEBELUM PAJAK TERHADAP PEMILIHAN METODE AKUNTANSI PERSEDIAAN (Studi Empiris Pada Perusahaan Sub Sektor Farmasi yang terdaftar di Bursa Efek Indonesia Periode 2012-2016) - Sri Ayem; Agus Pratama Putra Harjanta (AKUNTANSI DEWANTARA, 2018)
This study aims to examine the effect of firm size, inventory variability, managerial ownership, financial leverage, and profit before tax on the selection of inventory accounting methods. This study using secondary data with purposive sampling method. Data analysis techniques used logistic regression analysis with firm size, inventory variability, managerial ownership, financial leverage, and profit before variable tax (X) and selection of inventory accounting method as variable (Y). This study shows that partially inventory and profit before tax variables partially influence the selection of inventory accounting method while firm size, managerial ownership, and financial leverage have no effect on the selection of inventory accounting method. Simultaneously firm size, inventory variability, managerial ownership, financial leverage, and earnings before taxes together have a significant effect on the selection of inventory accounting method.